Where Enterprises Lead, People Follow? Links between Migration and German FDI - Claudia M. Buch; Jörn Kleinert; Farid Toubal (Kiel Institute for World Economics (IfW), 2003)
Globalization has affected the integration of markets through many different channels, including movements of factors and trade in goods. From a theoretical point of view, the interaction between the different channels of integration can take different forms. The aim of this paper is to analyze the interaction between different channels of integration empirically. More specifically, we use state-level German data to answer the question whether and how migration and FDI decisions and thus integration of labor and capital markets are linked. Our findings suggest that FDI and migration have similar determinants. Moreover, there is substantial evidence that factors cluster.
Keywords: F21; F0; F22; 330; migration; foreign direct investment; network effects; Direktinvestition; Internationale Wanderung; Network Externalities; Arbeitsmarkt; Finanzmarkt; Marktintegration; Schätzung; Teilstaat; Deutschland